The Correlation Between Total Calories And Protein Intake With Serum Albumin Level Of Post-Surgical Patients - Saputra, Ivan; Arifin, Fransiscus; Suyono, Handi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: Post-surgery diet is a set of foods that are given to patients after surgery. Nutritional management in post-surgical patients are often neglected despite the fact that patients require additional calories due to metabolic stress. Nutritional deficiency can impair wound healing since it is a process that requires protein to form collagen tissue. Aim: This study aims to determine the relationship between total calories and protein intake with serum albumin level of post-surgical patients. Methods: This study used an observational analytic design with cross-sectional approach. The sample was gathered using consecutive sampling technique. Study population were all post-surgical patients of Dr. Mohammad Soewandhie Hospital Surabaya aged 30-64 years whose medical records taken in June 2016. There are 32 respondents who met the inclusion criteria. Result: There was a significant correlation between the total calories intake with serum albumin level (r = 0.354; p = 0.047) and between total protein intake with serum albumin level (r = 0.545; p = 0.001). Conclusion: There is a positive correlation between total calories and protein intake with serum albumin level in post-surgical patients.